Effectiveness of Health Educational Program on Nurses' Knowledge toward Children Pneumonia in Al-Amara City Hospitals - Jassm, Ammar; Aziz, Afifa (Iraqi National Journal of Nursing Specialties, 2020)
Objective(s): The present study aims to evaluate the effectiveness of Health educational program on nurses' knowledge toward children pneumonia at Al-Amara City hospitals.. Methodology: A quasi –experimental study design two-study group (pretest-posttest 1 and posttest 2) carried out at Alzahrawy Hospital and Child and maternity hospital in Al Amara City to identify the effectiveness of the Health educational program on Nurses Knowledge toward Children pneumonia; the study was conducted between 1 of September 2019 to 1 of April 2020. A Purposive (Non-probability) sample is chosen for the present study. The size of sample is (60) nurses divided into two groups each one contains (30) nurses as control group and study group. The study group was exposed to the health educational program while the control group was not exposed to the health educational program.Results: The results of the study showed a clear positive effect of the program on the nurses' knowledge towards children pneumonia. The study results indicated that there are high significant differences for the study group between the pre-test and the post-test in the main aspects that have to do with the knowledge of nurses about children pneumonia.Recommendations : The study recommended the design and construction of an educational program for the nursing staff , whereby through the program it is emphasized that they are directed and familiarized with how to deal with children pneumonia, encourage the nursing owners to participate in educational programs to cover their various needs related to failures and obstacles to their practices and establish cooperative relations between the Ministry of Health and Higher Education to prepare this program